2010
DOI: 10.1037/a0017416
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ occupational and educational aspirations and expectations: Links to high school activities and adult educational attainment.

Abstract: This longitudinal study explored adolescents' future-oriented cognitions, current activities, and later educational attainment using data from 317 adolescents (55% female; mean age = 14.98 years, SD = 0.85) followed into early adulthood. Aspirations and expectations regarding work and education showed modest stability from year to year. Exploration of the reciprocal relations between these cognitions and adolescents' activities supported both unidirectional and bidirectional effects, with different patterns em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
239
1
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(274 citation statements)
references
References 23 publications
8
239
1
16
Order By: Relevance
“…Traditional status attainment research has shown that parents of higher socio-economic status have higher aspirations for their children, which are associated with higher aspirations among their offspring (Sewell & Hauser, 1975;Sewell, Hauser, & Wolf, 1980). High child aspirations, in turn, are associated with later academic and career success -a finding which has been consistently confirmed in different cultural and historical contexts (Beal & Crockett, 2010;Johnson & Reynolds, 2013;Kerckhoff, 1993;Kerckhoff, 2001;Schoon & Parsons, 2002;Sewell, Haller, & Ohlendorf, 1970) and for men and women (Mello, 2008;Schoon, Martin, & Ross, 2007;Sewell, Hauser, & Wolf, 1980). Furthermore, future-oriented aspirations can reduce the detrimental effect of parental socio-economic hardship and can be an important resource for young people from disadvantaged backgrounds to achieve against the odds (Schoon, 2006).…”
Section: Educational Achievement Orientation (Eao) As a Potential Medmentioning
confidence: 99%
“…Traditional status attainment research has shown that parents of higher socio-economic status have higher aspirations for their children, which are associated with higher aspirations among their offspring (Sewell & Hauser, 1975;Sewell, Hauser, & Wolf, 1980). High child aspirations, in turn, are associated with later academic and career success -a finding which has been consistently confirmed in different cultural and historical contexts (Beal & Crockett, 2010;Johnson & Reynolds, 2013;Kerckhoff, 1993;Kerckhoff, 2001;Schoon & Parsons, 2002;Sewell, Haller, & Ohlendorf, 1970) and for men and women (Mello, 2008;Schoon, Martin, & Ross, 2007;Sewell, Hauser, & Wolf, 1980). Furthermore, future-oriented aspirations can reduce the detrimental effect of parental socio-economic hardship and can be an important resource for young people from disadvantaged backgrounds to achieve against the odds (Schoon, 2006).…”
Section: Educational Achievement Orientation (Eao) As a Potential Medmentioning
confidence: 99%
“…Although the current paper did not include follow-up data, research has shown the expectations for the timing of transitions predict the actual timing of transitions (Beal & Crockett, 2010;Crockett & Beal, 2012;Mello, 2008). However, without longitudinal data, causality and directionality cannot be determined.…”
Section: Study Limitations Future Research and Implicationsmentioning
confidence: 94%
“…From the continuous research with 317 teenagers (age 15), Beal and Crockett (2010) indicated that the children's ambitions and expectations toward work and education were appropriately developed from teenagers to early adulthood. In addition, (Tracey, 2002;Tracey and Ward, 1998) revealed that children (ages 10-12) had relatively stable career expectations and the stability increased gradually with their increasing age.…”
Section: Itroductionmentioning
confidence: 99%